2003
DOI: 10.1002/app.13379
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐transfer‐agent‐aided polymerization and graft copolymerization of acrylamide

Abstract: ABSTRACT:The use of phase-transfer catalysts, with water-insoluble initiators, for polymerization and graft copolymerization reactions was explored. The polymerization of a water-soluble vinyl monomer, acrylamide (AAm), and the graft copolymerization of AAm onto a water-insoluble polymer backbone, isotactic polypropylene (IPP), with a waterinsoluble initiator, benzoyl peroxide (BPO), and a phasetransfer catalyst, tetrabutyl ammonium bromide (Bu 4 N ϩ Br Ϫ ), were carried out in a water/xylene binary solvent sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…In addition, such polymers have recently gained special interest in application of biosensors [4][5][6] and drug and bimolecular binding. 7 The growth and use of phase transfer catalyst (PTC) in polymerization and organic reactions is gaining remarkable progress in recent and past [8][9][10] ; they have been used in polycondensation, 11 anionic polymerization, 12 free-radical 13 and graft copolymerization, 14 and synthesis and modification of polymers, 15 and also several reports are existing in literature regarding the use of commercially available PTC in free-radical polymerization of various hydrophobic vinyl monomer in aqueous-organic twophase system. [16][17][18][19][20][21][22][23] In this technique, polymerization is initiated by the free radical arising from decomposition of complex of quaternary ammonium dication coupled with peroxy anion (QS 2 O 8 ) in organic phase extracted from aqueous phase, propagation occurs subsequently, and termination takes place by combination of the growing polymer chain radicals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such polymers have recently gained special interest in application of biosensors [4][5][6] and drug and bimolecular binding. 7 The growth and use of phase transfer catalyst (PTC) in polymerization and organic reactions is gaining remarkable progress in recent and past [8][9][10] ; they have been used in polycondensation, 11 anionic polymerization, 12 free-radical 13 and graft copolymerization, 14 and synthesis and modification of polymers, 15 and also several reports are existing in literature regarding the use of commercially available PTC in free-radical polymerization of various hydrophobic vinyl monomer in aqueous-organic twophase system. [16][17][18][19][20][21][22][23] In this technique, polymerization is initiated by the free radical arising from decomposition of complex of quaternary ammonium dication coupled with peroxy anion (QS 2 O 8 ) in organic phase extracted from aqueous phase, propagation occurs subsequently, and termination takes place by combination of the growing polymer chain radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The grafting of a monomer in any crystalline polymer takes place mainly in the amorphous zone of the parent backbone, but an increase in the percentage of grafting also affects the crystalline regions; hence, thermal stability of the parent polymer decreases, e.g., grafting of vinyl monomers to the PE [27] , isotactic PP [28] , Tefl on -FEP fi lm [29] , Tefzel fi lm [30] , etc. The decrease in thermal stability of isotactic PP -g -polyacrylamide is refl ected in Figure 5 Grafting may result in the formation of stable network to the polymerlike formation of stable imides from pendant amide groups in cotton -grafted methacrylamide [31] , which enhances the heat stability.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Choi and Lee 12 reported that the polymers, poly-(methyl methacrylate), prepared by phase transfer catalyzed polymerization, were found to have considerably high molecular weight and more uniform molecular weight distribution than the polymers prepared by conventional organic initiators such as AIBN (azobis isobutyronitrile) under similar reaction conditions. Polymerization of a water soluble monomer, acrylamide (AAm) and the graft copolymerization of AAm onto a water insoluble polymer backbone, isotactic polypropylene (IPP), using a water insoluble initiator, benzoyl peroxide (BPO), and a phase transfer catalyst, tetrabutylammonium bromide (Bu 4 N þ Br À ), were carried out in a water/ xylene binary solvent system by Kaur et al 13 Ooi et al 14 developed highly diastereo and enantioselective direct asymmetric aldol reaction of a glycinate Schiff's base with aldehydes catalyzed by chiral quaternary ammonium salts. Tetra-n-propyl and tetra-n-butyl ammonium bromates were used for the oxidation of a variety of aromatic amines to nitro compounds in high yields.…”
Section: Introductionmentioning
confidence: 99%